2022
DOI: 10.1186/s40621-022-00373-x
|View full text |Cite
|
Sign up to set email alerts
|

Size matters: How safety climate and downstream outcomes vary by fire department organization type

Abstract: Background Safety climate is an upstream predictor of safety behaviors (e.g., safety compliance), organizational outcomes (e.g., burnout, engagement), and safety outcomes (e.g., injuries). The Fire Service Organizational Culture of Safety (FOCUS) survey, which was psychometrically validated, measures the industry-specific safety climate of the US fire and rescue service. It is expressed by two factors, Management Commitment to Safety and Supervisor Support for Safety. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…The size of the department has been shown to modify the associations between safety climate and its subsequent outcomes, like safety behaviors and organizational outcomes, with safety climate generally being lower among career departments. 27 Consistent with the results found in our study, Srikanth et al 28 found that 23.8% of EMS providers were considering leaving the profession within 6 months. However, the study was only inclusive of a small sample from Puget Sound, Washington.…”
Section: Indicators Of Concernsupporting
confidence: 92%
See 3 more Smart Citations
“…The size of the department has been shown to modify the associations between safety climate and its subsequent outcomes, like safety behaviors and organizational outcomes, with safety climate generally being lower among career departments. 27 Consistent with the results found in our study, Srikanth et al 28 found that 23.8% of EMS providers were considering leaving the profession within 6 months. However, the study was only inclusive of a small sample from Puget Sound, Washington.…”
Section: Indicators Of Concernsupporting
confidence: 92%
“…These attributes may be skewing the results more positively among the FOCUS sample. Previous work by Geczik et al 27 showed that the size and organization type of a department impact Management Commitment to Safety scores (ie, the larger a department, the lower the score), but not Supervisor Support for Safety scores. The RAPID study affirms Geczik et al observing that Supervisor Support for Safety scores were similar between the samples and within the “maintenance zone”.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…FOCUS Supervisor Support for Safety refers to members' belief that their supervisors (company officers) value their safety based on communication, encouragement, and consequences (Taylor et al 2019 ). A recent analysis of the FOCUS beta-test survey wave, a geographically stratified random sample, identified that the mean Management Commitment to Safety scores for career fire departments were lower compared to combination and volunteer departments, however a similar variation for mean Supervisor Support for Safety scores were not observed (Geczik et al 2022 ). Safety behavior refers to the types of behaviors of workers that contribute to safety in the fire department, such as using the correct safety equipment (Neal and Griffin 2002 ).…”
Section: Introductionmentioning
confidence: 99%